2017
DOI: 10.1097/qad.0000000000001448
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of cancer observed in HIV/hepatitis C virus-coinfected patients versus HIV-monoinfected

Abstract: PLWH have a higher incidence of NADC than the general population and HCV-coinfection is associated with a higher incidence of NADC. These data justify the need for prevention strategies in these two populations and the importance of eradicating HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
13
1
2
Order By: Relevance
“…For example, 1 study showed the general loss of CD4 1 T cells correlated with the loss of EBV-specific CD8 1 T cells in subjects progressing to EBV-related NHL. 13 Coinfection with hepatitis B or C also appears to increase the risk of NHL [14][15][16] through a mechanism that includes chronic immune stimulation, although the precise pathway remains to be elucidated.…”
Section: Pathogenesis Of Hiv-associated Lymphomamentioning
confidence: 99%
“…For example, 1 study showed the general loss of CD4 1 T cells correlated with the loss of EBV-specific CD8 1 T cells in subjects progressing to EBV-related NHL. 13 Coinfection with hepatitis B or C also appears to increase the risk of NHL [14][15][16] through a mechanism that includes chronic immune stimulation, although the precise pathway remains to be elucidated.…”
Section: Pathogenesis Of Hiv-associated Lymphomamentioning
confidence: 99%
“…8 As with the general population, 38 many of these cancers are linked to lifestyle factors and comorbidities such as smoking and hepatitis C virus, both major sources of mortality among PLHIV. [39][40][41] Emphasis should be placed on targeting such behaviours and treating comorbidities such as chronic viral hepatitis in order to prevent cancer. pean cohorts were pooled in June 2014, within COHERE in EuroCoord.…”
Section: Discussionmentioning
confidence: 99%
“…As the cohort of PLHIV ages, they will be at increased risk of cancers not considered related to HIV that were previously rarely seen . As with the general population, many of these cancers are linked to lifestyle factors and comorbidities such as smoking and hepatitis C virus, both major sources of mortality among PLHIV . Emphasis should be placed on targeting such behaviours and treating co‐morbidities such as chronic viral hepatitis in order to prevent cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HCV therapies are not yet widely available in Myanmar, especially to vulnerable or indigent populations, and official guidance has only recently recommended using Direct Acting Anti-retrovirals (DAAs) rather than older, less expensive interferon based therapies that can interact with ART. Recent evidence has also suggested that people co-infected with HIV and HCV have a higher incidence of other illnesses, such as an almost two-fold risk of developing cancer [17]. The HIV/HCV co-infection rates seen in these fishermen, as well as the inter-related patterns of fishing, injecting drugs, and transactional sex, warrant further in depth study to better target HIV and HCV prevention and screening efforts, as well as better treatment of both diseases.…”
Section: Discussionmentioning
confidence: 99%